Crossref – Enabling African Research Item Discoverability Through The Research Nexus - Obanda, Johanssen; Ezeike, Ebuka; Havemann, Jo (My University, 2023)
This session is part of the AfricArXiv Webinar Series on Open Science for the Discoverability of African Research.
Watch the Recording https://africarxiv.pubpub.org/pub/wgadqkel#nbshhxs5t7c
Keywords: Research Nexus; Crossref; African research